Data flows and the digital economy: information as a mobile factor of production. Issue 1 (14th January 2019) - Mueller, Milton; Grindal, Karl
Abstract : Purpose: This paper aims to analyze the direction and balance of transnational information flows and look at how nonpriced digital information exchanges related to international trade in goods and services. Design/methodology/approach: The authors obtained quantitative data about Web-related data flows between countries and regions using Telegeography data on "Server Location as a Percentage of Top Websites." They then explore how those flows are correlated to trade in goods. Findings: Web traffic is highly transnational. More than half of the top 100 websites in 9 of the world's 13 sub-regions are hosted in the USA. More than 15 per cent of the top 100 websites in 9 of the 13 subregions are hosted in Western Europe. East Asia has the largest negative balance in the relationship between incoming and outgoing Web requests. The authors found a very strong negative correlation (−0.878) between Web traffic balances and the balance of trade in goods across all subregions. A similarly strong positive correlation was found with services trade; however, the incompleteness of the data does not allow for strong conclusions yet. Research limitations/implications: Further research is needed to correlate Web traffic flows with capital flows. The authors also do not have a well-developed theory to explain the strong negative correlation between information flows and goods trade. Practical implications: The data and analysis have useful implications for digital economy policy. It indicates that digital protectionism of the sort practice by China may succeed in increasing domestic producers' share of Web requests, but does not make them globally competitive. The strong negative correlation between the balance of unpriced Web information and the balance of trade in goods indicates interdependence rather than domination, challenging narratives that information flow imbalances are caused by market power of the big platforms. Social implications: The paper demonstrates the degree to which unpriced digital exchanges are transnational and how various countries are more or less globally competitive in the supply of information that the rest of the world finds attractive. Originality/value: No other published papers have used the data on website traffic data, and previous research has not explored empirically the correlation between information flows and goods trade.